Cytomegalovirus infection – selected aspects of clinical pathology - Kocięcki, Jarosław; Kocięcka, Wanda; Dmitriew, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
In this review short biological characteristics of human cytomegalovirus (CMV), the sources and its modes of transmission to human organisms, are presented. The authors described clinical pathology mainly of ocular organ and central nervous system in children with congenital cytomegalovirus infection and in acquired form of cytomegaly in adults with immunosupression (especially with HIV infection and AIDS). In review there are included contemporary diagnostic laboratory methods used in detection of CMV infection and in evaluation of clinical pathology